Duration of COVID-19: Data from an Italian Cohort and Potential Role for Steroids - Damiano D’Ardes; Michela Pontolillo; Lucia Esposito; Mara Masciarelli; Andrea Boccatonda; Ilaria Rossi; Marco Bucci; Maria Teresa Guagnano; Claudio Ucciferri; Francesca Santilli; Marta Di Nicola; Katia Falasca; et al. (Microorganisms, 2020)
The diffusion of SARS-CoV-2, starting from China in December 2019, has led to a pandemic, reaching Italy in February 2020. Previous studies in Asia have shown that the median duration of SARS-CoV-2 viral shedding was approximately 12–20 days. We considered a cohort of patients recovered from COVID-19 showing that the median disease duration between onset and end of COVID-19 symptoms was 27.5 days (interquartile range (IQR): 17.0–33.2) and that the median duration between onset of symptoms and microbiological healing, defined by two consecutive negative nasopharyngeal swabs, was 38 days (IQR: 31.7–50.2). A longer duration of COVID-19 with delayed clinical healing (symptom-free) occurred in patients presenting at admission a lower PaO2/FiO2 ratio (p < 0.001), a more severe clinical presentation (p = 0.001) and a lower lymphocyte count (p = 0.035). Moreover, patients presenting at admission a lower PaO2/FiO2 ratio and more severe disease showed longer viral shedding (p = 0.031 and p = 0.032, respectively). In addition, patients treated with corticosteroids had delayed clinical healing (p = 0.013).